Mortal kombat legends : Scorpion's revenge [videorecording (Blu-Ray + DVD)] - Spaulding, Ethan (Warner Bros. Entertainment, 2020)
A tournament is held between the champions of Outworld and Earthrealm, which will determine the fate of the world and all of mankind.